Toward new possibilities for library and information science : the use of social media in the 2018 West Virginia teachers' strike - Sikes, Scott (Emerald Publishing Limited, 2023)
The 2018 West Virginia teachers' strike in the United States exemplifies the changing shape of dissent and protest in the digital age. The use of social media has changed the ways such events develop and unfold, offering new tools for organizing, strategizing, generating large numbers of participants, and for communicating crucial information widely and quickly. Utilizing in-depth interviews with strike participants, 'Toward New Possibilities for Library and Information Science: The Use of Social Media in the 2018 West Virginia Teachers' Strike' takes a critical approach to understanding the role of social media in the 2018 teachers' strike, the significance of social media to the outcomes of the strike, and the importance of an Appalachian collective identity. It further proposes solutions for changing entrenched practices within library and information sciences education. In this way, it extends the scope and praxis of scholarship and education in information sciences.
Keywords: Libraries and society.; Libraries -- Technological innovations.; Social media and society.; Strikes and lockouts -- Libraries -- West Virginia.; Public libraries -- West Virginia.; Libraries and community.; Language Arts & Disciplines -- Library & Information Science -- General.; Public libraries.; elektronické knihy; electronic books